2003
DOI: 10.4049/jimmunol.171.7.3493
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Tolerance to Type II Collagen and Development of Arthritis in an Autologous Collagen-Induced Arthritis Model

Abstract: T cell recognition of the type II collagen (CII) 260–270 peptide is a bottleneck for the development of collagen-induced arthritis (CIA), an animal model of rheumatoid arthritis. We have earlier made C3H.Q mice expressing CII with glutamic acid instead of aspartic acid at position 266 (the MMC-C3H.Q mouse), similar to the rat and human CII epitope, which increases binding to MHC class II and leads to effective presentation of the peptide in vivo. These mice show T cell tolerance to CII, but also develop severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…This has also been observed in the C3H.Q strain (28) and probably reflects an intrinsic phenotype of the genetic background. It could be speculated that introduction of the Ncf1 mutation will lead to a more efficient T cell response, possibly via IL-17, that could stimulate the anti-CII B cell response to reach arthritogenic levels earlier in MMC.B10.DR4.Ncf1* mice compared with MMC.C3H.DR4 mice.…”
Section: Discussionmentioning
confidence: 83%
“…This has also been observed in the C3H.Q strain (28) and probably reflects an intrinsic phenotype of the genetic background. It could be speculated that introduction of the Ncf1 mutation will lead to a more efficient T cell response, possibly via IL-17, that could stimulate the anti-CII B cell response to reach arthritogenic levels earlier in MMC.B10.DR4.Ncf1* mice compared with MMC.C3H.DR4 mice.…”
Section: Discussionmentioning
confidence: 83%
“…It is conceivable that the genetic background may alter the relative importance of various regulatory populations in acquiring tolerance to self-Ags. In fact, we have recently shown that rat CIIspecific tolerance in MMC mice is differently regulated in mice of different genetic background (43), where MMC mice on the B10.Q background or on the F 1 background of B10.Q ϫ C3H.Q appear completely resistant to CIA. Therefore, it would be of interest to investigate whether the rat CII-specific tolerance in MMC mice on the B10.Q background is more dependent on CD4 ϩ CD25 ϩ regulatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not explicitly determine whether the salivary IgA anti-CCP antibodies were di-or polymeric molecules containing joining chain and From studies on experimental autoimmune diseases, including collagen type II (CII) induced arthritis (CIA), systemic tolerance after mucosal immunisation with autoantigen is well-known (Weiner et al 2011). CIA in mice, including 'humanised' animals transgenic for HLA-DRB1/shared epitope (SE) (Bäcklund et al 2003), are still prevailing experimental models for RA. Based upon such experimental settings, it was long suspected that systemic immunisation against CII is crucial also for the development of RA in man.…”
Section: Discussionmentioning
confidence: 99%